In Situ and Simultaneous UV-vis/SAXS and UV-vis/XAFS Time-Resolved Monitoring of ZnO Quantum Dots Formation and Growth - Caetano, Bruno Leonardo [UNESP]; Santilli, Celso Valentim [UNESP]; Meneau, Florian; Briois, Valerie; Pulcinelli, Sandra Helena [UNESP] (Amer Chemical Soc, 2011)
The processes of formation, aggregation, and growth of ZnO quantum dots (Qdot) induced by the addition of KOH solution ([OH]/[Zn] = 0.5) to the zinc oxy-acetate ethanolic solution at 40 degrees C were examined in depth by in situ and simultaneous time-resolved monitoring of UV-vis absorption spectra combined with small-angle X-ray scattering (SAXS) and with X-ray absorption fine structure (XAFS) measurements. XAFS results recorded at the Zn K-edge evidence the presence of both the zinc oxy-acetate precursor and the ZnO nanocrystals. Each XAFS spectrum could be described by a linear combination of each reference spectra, the composition evolving from similar to 47% to similar to 82% of ZnO from the beginning to the end of time monitoring. The time evolution of the UV vis spectra shows a pronounced red shift of the excitonic peak during the first 100 min of reaction, characterizing the ZnO Qdot growth. The SAXS curves obtained simultaneously with the UV vis spectra follow the Porod law at the large q-range, indicating the presence of well-defined smooth surface particles. At the intermediate q-range, the SAXS profiles evolve from a Guinier pattern, typical of diluted sets of aggregates, to a power law dependence characteristic of fractal structures. For reaction times higher than 400 min, the slope of the fractal region of SAXS curves reaches a value characteristic of diffusion controlled cluster cluster aggregation process. The results of this in situ and combined techniques investigation show that the kinetic of formation of colloidal ZnO nanocrystal is a step process composed of four main stages: (i) ZnO Qdot nucleation and growth; (ii) growth of compact ZnO Qdot aggregates; (iii) growth of fractal aggregates; and (iv) secondary nucleation and fractal aggregates growth.